Immediate effects of myofascial release or taping on tissue and plantar pressure in diabetes - Kablan, Nilufer; Alaca, Nuray; Gercek, Nejla; Elarslan, Serkan; Tatar, Yasar (Journal of the Pakistan Medical Association, 2025)
Objective: To investigate the immediate effects of myofascial release and kinesiologic taping on the biomechanical properties of plantar fascia and Achilles tendon in type 2 diabetes mellitus patients, and to analyse changes in plantar pressure distribution following the intervention. Method: The prospective case-control study was conducted at the Marmara University, Turkiye, from February 1 to May 27, 2021, and comprised male type 2 diabetes mellitus patients aged 35-65 years in group A and healthy controls matched for age and gender in group B. Myofascial release with the help of a foam roller was applied to the plantar fascia on one foot, while kinesiologic taping using the ligament technique was applied on the other foot. Stiffness and elasticity of the plantar fascia and Achilles tendon, as well as total contact area and peak contact pressure were assessed at the baseline, immediately after the intervention, and 30 minutes post-intervention. Data was analysed using SPSS 22. Results: Of the 26 male subjects, 13(50%) were in group A with mean age 57.77±4.81 years (range: 48-65 years). There were 13(50%) controls in group B with mean age 54.69±7.4 years (range: 37-59 years) (p=0.05). Stiffness and elasticity values were not significantly different between the groups at baseline (p>0.05). Myofascial release application increased plantar fascia stiffness in group B (p=0.001), whereas in group A, it increased the contact area (p=0.018) and pressure (p=0.032) of the forefoot-medial, and decreased the peak contact pressure of the hind foot (p=0.032) at 30 minutes post-intervention. In group A, kinesiologic taping application decreased the hind foot contact area and pressure (p=0.032) without altering the forefoot dynamics (p>0.05). Conclusion: Although kinesiologic taping had a positive effect and myofascial release had a negative effect on plantar fascia, the impact was unsteady. Key Words: Fascia, Achilles tendon, Diabetes mellitus, Type 2, Athletic tape, Myofascial release treatment.